UJI LACK OF FIT DENGAN PENDEKATAN UJI F MELALUI STATISTIK UJI WALD-TYPE PADA RANCANGAN BLOCKED RESPONSE SURFACE - , Syita Fatih 'Adna ([Yogyakarta] : Universitas Gadjah Mada, 2013)
In this thesis, lack of fit test in blocked response surface design using approximation F-test is investigated. Approximation -test is done through Wald-type test statistics with constructing Wald-type pivot. Then, we determine E(F) and var(F), and note that F is Wald-type pivot. By using Kenward-Roger modification,E(F*) and var(F*), also estimating scala factor and denominator degree of freedom m, obtained F* = AF approaching (l,m) distribution. Finally, lack of fit test can be perform using F* test statistics.